1969
DOI: 10.1079/bjn19690019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intravenous infusions of triglycerides on the secretion of milk fat in the cow

Abstract: I. Artificial emulsions of nine synthetic triglycerides ranging from tripropionin to triolein were given as continuous infusions into the jugular vein of lactating cows for periods of z days.The effects of these infusions on the composition of blood lipids and on the secretion of the component fatty acids in milk were examined.2. Tricaproin, tricaprylin, tripelargonin, tricaprin, trilaurin, trimyristin and triolein, in contrast to tripropionin and tributyrin, increased the yields in milk of the acid contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1969
1969
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…HALL, B. TUCKLEY AND D. MILLARD 1969 Greenford, England) was given at the daily rate of 500 g oil for z days. The cod-liver oil emulsions were prepared in the laboratory as previously described (Storry, Tuckley & Hall, 1969) from either unfractionated cod-liver oil or an ethyl ester fraction of cod-liver oil rich in polyunsaturated acids (Ethive; British Codliver Oils (Hull & Grimsby) Ltd), both specially prepared to have a low peroxide content. The cod-liver oil and Ethive emulsions were infused at the daily rate of 400 g for 3 days.…”
Section: I74mentioning
confidence: 99%
See 1 more Smart Citation
“…HALL, B. TUCKLEY AND D. MILLARD 1969 Greenford, England) was given at the daily rate of 500 g oil for z days. The cod-liver oil emulsions were prepared in the laboratory as previously described (Storry, Tuckley & Hall, 1969) from either unfractionated cod-liver oil or an ethyl ester fraction of cod-liver oil rich in polyunsaturated acids (Ethive; British Codliver Oils (Hull & Grimsby) Ltd), both specially prepared to have a low peroxide content. The cod-liver oil and Ethive emulsions were infused at the daily rate of 400 g for 3 days.…”
Section: I74mentioning
confidence: 99%
“…At 12.00 h on each day of the experiment samples of blood were taken through a cannula situated in the jugular vein opposite to that used for the infusion, and the individual lipid classes in blood plasma were determined by thin-layer chromatography as previously described (Storry et al 1969). The fatty acid composition of the plasma triglycerides was determined by gas-liquid chromatography of the methyl esters with a Perkin Elmer model F I I gas chromatograph in the experiments with soya-bean oil (Storry et al 1967) and a Pye Argon gas chromatograph with columns 10% Apiezon L on 100-120 mesh acid-alkali washed celite at 230° in the experiments with cod-liver oil and Ethive.…”
Section: I74mentioning
confidence: 99%
“…An increase of polyunsaturated fatty acids in the blood lipids during the feeding of a milk fat-depressing diet is only mentioned occasionally (QURESHI et al 1972). In other experiments, an increase of oleic acid in the blood triacylglycerols is reported (ANNISON et al 1974;ASKEW et al 1971), while others observed increases of both oleic and linoleic acid (STORRY and SUTTON 1969). O n high-concentrate diets the amount ofpolyunsaturated fatty acids is higher than in high-roughage diets.…”
Section: )mentioning
confidence: 78%
“…VLDL, which are mainly secreted by the liver, are hydrolysed by lipoprotein lipase (LPL) at the endothelial surface in adipose tissue and muscle (Fielding and Havel, 1977) and the rate of uptake of fatty acid is related to the concentration of plasma TG. Plasma TG forms only a small proportion of total plasma lipids in sheep and diet does not influence the level (Storry, Tuckley and Hall, 1969). Though the concentrations are low t Present address: School of Science, University of Waikato, Hamilton, New Zealand.…”
Section: Introductionmentioning
confidence: 99%